The Nubdzatul Bayan Mentoring Program as a Strategy to Strengthen the Basic Competencies of Students in Overcoming Difficulties in Understanding the Kitab Kuning - Moh Kamil; Moh. Mohlas; Najiburrahman Najiburrahman; Akmal Mundiri; Moch. Tohet (Communautaire: Journal of Community Service, 2025)
This study aims to examine the effectiveness of the Nubdzatul Bayan mentoring program as a medium to strengthen students' basic competencies in understanding Kitab Kuning at Ma'had Aly. This program is designed to improve students' understanding of the basics of Arabic science and Kitab Kuning learning methodology, which are often the main obstacles in understanding classical texts. The research method used is a qualitative approach with in-depth interviews and participatory observation to collect data on the implementation and impact of the mentoring program on students. The results of the study indicate that the Nubdzatul Bayan mentoring program is effective in improving students' basic competencies, especially in terms of mastery of nahwu science which is the basis for studying Kitab Kuning. This program also succeeded in increasing students' confidence in understanding Kitab Kuning texts. The implications of this study are the importance of developing a structured mentoring program based on students' basic needs to improve their understanding of Kitab Kuning, and can be applied in other Islamic boarding schools as a more effective teaching model.